2014
DOI: 10.4187/respcare.03335
|View full text |Cite
|
Sign up to set email alerts
|

What Is the Potential Role of Transcutaneous Carbon Dioxide in Guiding Acute Noninvasive Ventilation?

Abstract: BACKGROUND: Transcutaneous carbon dioxide (P tcCO 2 ) monitoring is rarely used in the acute hospital setting, where serial samples of arterial blood are instead taken to measure carbon dioxide tension (P aCO 2 ). In this pilot observational study, we assessed the potential of P tcCO 2 monitoring to calculate pH and guide management of acute noninvasive ventilation (NIV). METHODS: Ten subjects with acute hypercapnic respiratory failure were recruited. All had arterial lines placed to guide acute NIV. P tcCO 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…In critically ill subjects as Rodriguez et al 16 suggest, transcutaneous arterial carbon dioxide is probably more useful as a trend-monitoring tool to predict changes in P aCO 2 than as a single measurement. In the same way, van Oppen et al 17 in a pilot study demonstrate that P tcCO 2 provides a continuous and reliable tool and also allows pH prediction.…”
Section: Discussionmentioning
confidence: 81%
“…In critically ill subjects as Rodriguez et al 16 suggest, transcutaneous arterial carbon dioxide is probably more useful as a trend-monitoring tool to predict changes in P aCO 2 than as a single measurement. In the same way, van Oppen et al 17 in a pilot study demonstrate that P tcCO 2 provides a continuous and reliable tool and also allows pH prediction.…”
Section: Discussionmentioning
confidence: 81%
“…As mentioned by van Oppen et al, 4 further research is necessary to validate the use of the pH algorithm described. What might be interesting to consider is whether treatment of this small number of subjects would have been altered had the authors simply monitored signs and symptoms, as mentioned previously.…”
Section: See the Original Research On Page 484mentioning
confidence: 99%
“…van Oppen et al 4 found that subjects who required NIV preferred transcutaneous to arterial blood gas monitoring. The authors referred to arterial blood gas sampling as being more time-consuming and painful for subjects.…”
Section: See the Original Research On Page 484mentioning
confidence: 99%
See 2 more Smart Citations